Diatom/dinoflagellate cyst/highly branched isoprenoid lipid/algal pigment/geochemistry data sets from Belcher Islands Archipelago, Hudson Bay - Luostarinen, Tiia; Weckström, Kaarina; Ehn, Jens K; Kamula, Michelle; Burson, Amanda; Diaz, Aura; Massé, Guillaume; McGowan, Suzanne; Kuzyk, Zou Zou; Heikkilä, Maija (PANGAEA, 2023)
Datasets collected during a field campaign in the Belcher Islands Archipelago, Hudson Bay, Canada, during spring and summer 2019 including sea ice, water column, sediment trap and surface sediment samples that were analysed for diatoms, dinoflagellate cysts, highly branched isoprenoid lipids, pigments and geochemistry. The sea ice samples were collected using a Kovacs Mark II core barrel with an internal diameter of 9 cm, and the bottom 5 cm of the sea-ice cores were used for analysis on each sampling day. The water sampling was conducted using a plankton net (Ø 18 cm, 10 µm, 30-m net haul; diatoms) and a 2,5 L Kemmerer water sampler (pooled sample from 2.5-, 5-, 10-, 15-, 20-, 25- and 30-metre depths; highly branched isoprenoid lipids). For sediment trap samples, an automated Gurney Instruments Baker-style, cylindrical sediment trap (aperture 0.032 m2) was deployed at 40-m depth, 30-m above the seafloor and the rotation for the trap was set to 8-day intervals. The surface sediment sample was collected using a Kajak-Brinkhurst gravity corer. The under-ice salinities and temperatures were measured by using with RBR Concerto® and CastAway-CTD® sensors.
Keywords: Diatom; Dinoflagellate cysts; Highly branched isoprenoid (HBI) biomarkers; Hudson Bay; sediment trap